One size does not fit all for parent-mediated autism interventions: A randomized clinical trial. (February 2023) - Roberts, Megan Y; Sone, Bailey J; Jones, Maranda; Grauzer, Jeffrey; Sudec, Laura; Stern, Yael S; Kwok, Elaine; Losh, Molly; Kaat, Aaron
Coaching parents to use language facilitation strategies improves long-term language outcomes for autistic children. To optimize parent-mediated interventions, more studies need to explore factors that influence parents' learning. This study involved 119 autistic children (18–48 months) and their biological mothers enrolled in a single-site, factorial randomized clinical trial. Mothers were taught to use one of two types of language facilitation strategies (responsive or directive) during eight weekly, hour-long instructional sessions. We explored the impact of (a) type of language facilitation strategy, (b) maternal Broad Autism Phenotype (subclinical traits of autism spectrum disorder), and (c) preintervention strategy use on mothers' outcomes measured immediately and 3 months after intervention sessions. At postintervention, mothers who learned responsive strategies demonstrated significantly greater use of taught strategies than mothers who learned directive strategies ( d  = 0.90, 95% CI =[0.47, 1.32]). Mothers' use of taught strategies did not differ by Broad Autism Phenotype status. However, a significant two-way interaction was found between preintervention strategy use and Broad Autism Phenotype status on taught strategy use ( F (1, 107) = 6.04, p   =  0.016, Δ R 2  = 0.053). Findings suggest that strategy type, maternal Broad Autism Phenotype status, and preintervention strategy use may be important factors to be considered to individualize parent-mediated interventions. Lay Abstract: Parent-mediated interventions support parents' use of language facilitation strategies to improve their autistic child's communication and language development. To improve the effectiveness of parent-mediated interventions, it is important to individualize interventions. This article evaluates how different components of parent-mediated interventions and mothers' learning styles influence the effectiveness of the intervention. In a randomized clinical trial, mothers were taught to use one of two types of language facilitation strategies: responsive and directive. Mothers' learning styles were characterized by the Broad Autism Phenotype (BAP) and their natural tendency to use language facilitation strategies before intervention. Findings suggest that it was easier for all mothers (irrespective of learning style) to use responsive strategies compared to directive strategies. In addition, mothers with learning styles that were not consistent with the BAP were more likely to benefit from the intervention if they did not naturally use strategies before the intervention. In contrast, mothers with learning styles that were consistent with the BAP were more likely to benefit from the intervention if they did naturally use strategies before the intervention. Teaching mothers to use responsive strategies results in greater strategy use. Consideration of BAP and mothers' natural use of language facilitation strategies may inform intervention individualization.